High-level mosaic trisomy 21 at amniocentesis in a pregnancy associated with positive NIPT for trisomy 21, prenatal progressive decrease of the trisomy 21 cell line, acute fatty liver of pregnancy and intrauterine fetal death in late gestation - Chih-Ping Chen; Liang-Kai Wang; Fang-Tzu Wu; Yen-Ting Pan; Peih-Shan Wu; Wen-Lin Chen; Meng-Shan Lee; Wayseen Wang (Elsevier, 2023)
Objective: We present high-level mosaic trisomy 21 at amniocentesis in a pregnancy associated with positive non-invasive prenatal testing (NIPT) for trisomy 21, prenatal progressive decrease of the trisomy 21 cell line, acute fatty liver of pregnancy and intrauterine fetal death (IUFD) in late gestation. Case report: A 32-year-old, primigravid woman underwent amniocentesis at 17 weeks of gestation because of positive NIPT for trisomy 21 at 12 weeks of gestation. This pregnancy was conceived by in vitro fertilization. She did not have obesity, diabetes mellitus, hepatic biliary disorders and preeclampsia. Amniocentesis revealed a karyotype of 47,XY,+21[10]/46,XY[11], and array comparative genomic hybridization (aCGH) analysis on uncultured amniocytes revealed the result of arr (21) × 2-3. She was referred for genetic counseling, and repeat amniocentesis performed at 21 weeks of gestation revealed the karyotype of 47,XY,+21[10]/46,XY[28]. The parental karyotypes and fetal ultrasound findings were normal. Simultaneous molecular analysis on uncultured amniocytes showed no uniparental disomy 21, but a maternal origin of trisomy 21 by quantitative fluorescent polymerase chain reaction (QF-PCR) and the result of arr 21q11.2q22.3 × 2.5 by aCGH analysis. At 27 weeks of gestation, she underwent a third amniocentesis, of which conventional cytogenetic analysis revealed the result of 47,XY,+21[5]/46,XY[17] in cultured amniocytes, and aCGH analysis revealed arr 21q11.2q22.3 × 2.48, and interphase fluorescence in situ hybridization (FISH) analysis revealed 39% (39/100 cells) mosaicism fro trisomy 21 in uncultured amniocytes. At 36 weeks of gestation, the woman suffered from a sudden onset of acute fatty liver and IUFD. A 3522-g male baby was delivered without Down syndrome phenotype. The umbilical cord had a karyotype of 47,XY,+21[10]/46,XY[30]. aCGH analysis on the skin and placenta showed arr 21q11.2q22.3 × 2.73 and arr 21q11.2q22.3 × 2.75, respectively. QF-PCR analysis of umbilical cord, placenta and skin showed a maternal origin of trisomy 21. Conclusion: High-level mosaic trisomy 21 at amniocentesis can be associated with prenatal progressive decrease of the trisomy 21 cell line in cultured amniocytes and perinatal fetal mortality and maternal morbidity.